Sequential or Combination Treatments as Rescue Therapies in Immunocompromised Patients with Persistent SARS-CoV-2 Infection in the Omicron Era: A Case Series - Bianca Maria Longo; Francesco Venuti; Alberto Gaviraghi; Tommaso Lupia; Fabio Antonino Ranzani; Andrea Pepe; Laura Ponzetta; Davide Vita; Tiziano Allice; Vanesa Gregorc; Pio Manlio Mirko Frascione; Francesco Giuseppe De Rosa; et al. (MDPI AG, 2023)
Prolonged SARS-CoV-2 infections are widely described in immunosuppressed patients, but safe and effective treatment strategies are lacking. We aimed to outline our approach to treating persistent COVID-19 in patients with immunosuppression from different causes. In this case series, we retrospectively enrolled all immunosuppressed patients with persistent SARS-CoV-2 infections treated at our centers between March 2022 and February 2023. Patients received different sequential or combination regimens, including antivirals (remdesivir, nirmatrelvir/ritonavir, or molnupiravir) and/or monoclonal antibodies (mAbs) (tixagevimab/cilgavimab or sotrovimab). The main outcome was a complete virological response (negative SARS-CoV-2 RT-PCR on nasopharyngeal swabs) at the end of treatment. Fifteen patients were included as follows: eleven (11/15; 73%) with hematological disease and four (4/15; 27%) with recently diagnosed HIV/AIDS infection. Six patients (6/15; 40%) received a single antiviral course, four patients (4/15; 27%) received an antiviral and mAbs sequentially, and two patients (13%) received three lines of treatment (a sequence of three antivirals or two antivirals and mAbs). A combination of two antivirals or one antiviral plus mAbs was administered in three cases (3/15, 20%). One patient died while still positive for SARS-CoV-2, while fourteen (14/15; 93%) tested negative within 16 days after the end of treatment. The median time to negativization since the last treatment was 2.5 days. Both sequential and combination regimens used in this study demonstrated high efficacy and safety in the high-risk group of immunosuppressed patients.